Burden of Proof for the Illegal Immissions as Prerequisite of In Rem Removal Claim - Knežević, Marko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Abstract: This paper examines the question of the burden of proof for the facts that imply illegal immission as prerequisite of in rem removal claim. The approach is different to the standard doctrine and it is in according to the general rule of the burden of proof in litigation – so called modified norm theory. In the centre of the attention is distinction of so called constitutive and impeditive facts, and criteria for distinction. The implementation of modified norm theory regarding issue of this paper shows that primal distinguishing point is not suitable, so the other modification methods should be applied, in order to get the answer. Key words: burden of proof, claim, in rem removal claim, immissions